Monitoring the behavior of imazalil and its metabolite in grapes, apples, and the processing of fruit wine at enantiomeric level. (21st March 2021) - Li, Runan; Pan, Xinglu; An, Xiaokang; Wang, Kuan; Dong, Fengshou; Xu, Jun; Liu, Xingang; Wu, Xiaohu; Zheng, Yongquan
Abstract: BACKGROUND: Imazalil is widely used in agriculture, which may pose a threat to food safety. This study aimed to investigate the fate of imazalil and its main metabolite, R14821 (imazalil‐M), in field grapes and apples, and in the processing of fruit wine at the enantiomeric level. RESULTS: Analysis method was established to determine imazalil and imazalil‐M enantiomers in grape, apple, fruit wine and pomace. The method showed acceptable recoveries of 71.6–99.9% and precision with relative standard deviation of 0.3–11.7%. Processing factors (PFs) were 0.15–0.40 (for imazalil enantiomers) and <0.13–0.83 (for imazalil‐M enantiomers) during the wine‐making process. The PFs after individual steps including washing, peeling, fermentation, and clarification were all less than 1. No enantioselective dissipation of imazalil was found in grapes under field conditions with half‐lives of 23.82–24.49 days. R ‐(−)‐imazalil degraded slightly faster than S ‐(+)‐imazalil in apples under field conditions with half‐lives of 9.82–10.09 days. S ‐(+)‐imazalil‐M preferentially degraded in field grapes and apple. No significant enantioselectivity of imazalil and imazalil‐M was observed during the wine‐making process. The enantiomeric fraction (EF) values of imazalil were 0.484–0.511 and 0.509–0.522 in grape wine and cider, respectively. The EFs were 0.484–0.501(in grape wine) and 0.484–0.504 (in cider) for imazalil‐M. CONCLUSION: The results showed that the wine‐making process could reduce imazalil and imazalil‐M residues in grapes and apples. The finding of non‐enantioselectivity of imazalil during the processing of fruit wine was useful for accurate risk assessment for imazalil in raw and processing fruits. © 2021 Society of Chemical Industry.